Inside Front Cover: Mesogens with aggregation‐induced emission properties: Materials with a bright future. Issue 1 (22nd February 2022) - Voskuhl, Jens; Giese, Michael
Abstract : Shine bright like a liquid crystal : In this review the recent developments in the fabrication of luminescent liquid crystalline materials are summarized and a first glance on potential applications is given.